Influência das leis do esporte nacional na governança corporativa das confederações e federações dos esportes olímpicos durante o período de 1941 a 2013 - Morales, Clarice (2015)
This study investigates the influence of Brazilian National Sports Laws in the governance of Olympic Sports Confederations and Federations, between 1941 and 2013. These organizations have demonstrated management difficulties according to governance principles, such as transparency, social responsibility, ethics and accountability, receiving criticism from diverse sport’s stakeholders. The Brazilian national sport system was implemented by the Decree-Law n. 3199 of 14/08/1941, which created and regulated national and state sports organizations until the 80’s. With the new Constitution of 1988, sports became law definitive and, according to the Law no. 9.615 of 1998, high performance sports continued to be monitored and regulated by the government. The central question of this study was: how the Brazilian national sports laws have influenced in the governance of Confederations and Federations of Olympic Sports between 1941 and 2013? The methodology employed is qualitative, exploratory, descriptive, documental and bibliographic; two confederations and two federations were taken as case studies. The triangulation of documentary evidence, semi-structured interviews and theories corporate governance and management in the Third Sector brought important results and expanded the discussion towards a more complex view. As contributions this study chronologically presents the concepts, functions and the legal and management control of the state over the governance of sports organizations, from 1941 until 2013. It also studies the characteristics of sports organizations, as the Third Sector and the applicability of the concepts and governance principles for understanding of management needs, proposing some practices. Based on documentary studies, the theoretical framework and interviews concluded that the laws influenced and influence the governance of sports organizations.